AN ANALYSIS ON ENGLISH LOANWORDS IN AKB48 SONGS - Michael Dony Danardana (ELTR Journal, 2018)
There are vast amount of English loanwords in Japanese language than other languages. It is in contradistinction to the fact that Japanese language itself has a distant difference in terms of phonology, syntax, pragmatics and discourse from English. Certainly, the borrowing of English words in Japanese language involves some loanword transformations in order to fit its language system. In order to discover those, first, the researcher reviews the relevant literature of the loanword transformations in Japanese. Then, the researcher analyses the types of loanwords transformation from English loanwords production of 5 AKB48 songs. Document analysis was used in this research. The result shows that phonological transformation is the dominant type used in the songs.